Circadian clocks and memory: time-place learning - Mulder, Cornelis K.; Gerkema, Menno P.; Van Der Zee, Eddy A. (Frontiers in Molecular Neuroscience, 2013)
Time-Place learning (TPL) refers to the ability of animals to remember important events that vary in both time and place. This ability is thought to be functional to optimize resource localization and predator avoidance in a circadian changing environment. Various studies have indicated that animals use their circadian system for TPL. However not much is known about this specific role of the circadian system in cognition. This review aims to put TPL in a broader context and to provide an overview of historical background, functional aspects and future perspectives of TPL. Recent advances have increased our knowledge on establishing TPL in a laboratory setting, leading to the development of a behavioral paradigm demonstrating the circadian nature of TPL in mice. This has enabled the investigation of circadian clock components on a functional behavioral level. Circadian TPL was found to be Cry clock gene dependent, confirming the essential role of Cry genes in circadian rhythms. In contrast, preliminary results have shown that circadian TPL is independent of Per genes. Circadian system decline with aging predicts that circadian TPL is age sensitive, potentially qualifying TPL as a functional model for episodic memory and aging. The underlying neurobiological mechanism of TPL awaits further examination. Here we discuss some putative mechanisms.